Influence of Absorption of Thermal Radiation in the Surface Water Film on the Characteristics and Ignition Conditions; MATEC Web of Conferences; Vol. 72 : Heat and Mass Transfer in the System of Thermal Modes of Energy – Technical and Technological Equipment (HMTTSC-2016) - Syrodoy S. V. Semen Vladimirovich (2016, 2016)
Title screen